Idārah Tarsyīh Nādy Al-Kindī Fī Taṭwīr Al-Kafā-ah Al-Lugawiyyah Al-‘Arabiyyah - Muhammad Riki Sulthonul Fata; Muhammad Bagus Ainun Najib; Khowarizmi Abdul Karim (Lisanudhad: Jurnal Bahasa, Pembelajaran, dan Sastra Arab, 2019)
AbstractThis study aims to determine the regeneration management of al-Kindy members in the Arabic development at UIN Maulana Malik Ibrahim Malang. The objectives of this study are to describe (1) the characteristics of al-Kindy members (2) management cadre members of al-Kindy (3) supporting factors and inhibitors of cadre management al-Kindy members. This study uses a qualitative descriptive approach, and data collection techniques in this study are observation, interviews, and documentation. Based on the results of research conducted by researchers that the most important points that exist in this study are as follows: (1) the characteristics of al-Kindy members are Arabic Education students at UIN Maulana Malik Ibrahim Malang who have basic Arabic skills, must take selection tests and have high commitments to participate in Al-Kindy’s program and to take part in the Arabic Language competition (2) the regeneration management of al-Kindy members is planning, organizing, implementing and monitoring (3) the supporting factors for the management of cadre regeneration are the high enthusiasm and commitment of Al-Kindy members about the importance of Arabic, as well as the support and motivation of the al-kindy senior members and lecturers of Arabic Language Education, and the inhibiting factors for cadre management are lack of facilities and financial support.Keywords: Management Cadre, Arabic Club, Arabic Competence, Arabic Debate إدارة ترشيح أعضاء نادى الكندي في تطوير الكفاءة اللغوية العربيةمحمد ريقي سلطان الفتى، محمد باغوس عين النجيب، خوارزمي عبد الكريمجامعة مولانا مالك إبراهيم الإسلامية الحكومية مالانجrikifata@gmail.com, boledclub@gmail.com, khevarizmey@gmail.com الملخصإن هدف هذا البحث لمعرفة إدارة ترشيح أعضاء نادى الكندى عند تطوير اللغة العربية بجامعة مولانا مالك إبراهيم الإسلامية الحكومية بمالانق. وهدف هذا البحث لتصوير عدة الأمور الموجودة في نادى الكندى منها 1) خصائص أعضاء نادى الكندى 2) إدارة ترشيح أعضاء الكندى 3) العوامل الدافعة والعوامل العائقة  عند عملية إدارة ترشيح أعضاء نادى الكندء. وأما مدخل البحث المستخدم هو المدخل الوصفي الكيفي، والطريقة جمع البيانات المستخدمة هي الملاحظة والمقابلة والوثائق التي تتعلق بأعضاء نادى الكندى. بالنسبة إلى نتيجة الحبث فنقطة هامة عند هذا البحث هي 1) إن خصائص أعضاء نادى الكندى هي طالب قسم تعليم اللغة العربية بجامعة مولانا مالك إبراهيم الإسلامية الحكومية بمالانق حيث أنه لديه كفاءة اللغة العربية الأساسية، ولابد عليه أن يشترك اختبار تحديد المستوى، وله همة عالية لاشتراك الأنشطة الموجودة في هذه النادى والمسابقات العربية. 2) وأما إدارة ترشيح أعضاء الكندى فهي التخطيط والإدارة والتفيذ والمراقبة 3) وأما العامل الدافع عند إدارة ترشيح أعضاء الكندى فهو وجود الوعى والهمة العالية لهم عن أهمية اللغة العربية ووجود التأييد والمحثة من الأعضاء السابقين ومحاضري قسم تعليم اللغة العربية. وأما العامل العائق عند إدارة ترشيح أعضاء الكندى فهو عدم الوسائل الدافعة وعدم المصارف لتوفير حاجة الأعضاء.الكلمات المفتاحية : إدارة الترشيح، نادى اللغة العربية، كفاءة اللغة العربية، المناظرة العلمية العربية